TLC Profiling and Phytochemical Screening of Various Extracts of Ochna integerrima (Lour.) Merr. from Kog Dong Keng Forest, Thailand - Sombat Appamaraka; Chadaporn Senakun; Surapon Saensouk (Pharmacognosy Journal, 2022)
Introduction: Ochna integerrima (Lour.) Merr. belongs to family Ochnaceae, and it is a traditionally important herb in Southeast Asia. The objective of this study was to investigate the phytochemical compounds of various extracts from six samples. Methods: Thin Layer Chromatography (TLC) of the hexane, dichloromethane and 70% ethanol extracts were performed for five important phytochemicals namely, alkaloids, flavonoids, terpene, cardiac glycosides and anthraquinone. Results: Terpene was found in all the samples that were extracted from all extracts, while cardiac glycosides and anthraquinone did not occur in all samples that were extracted from all extracts. Flavonoids were observed in all samples that were only extracted with dichloromethane, whereas it was found in some samples from the other extracts. The hexane extract compound was found in alkaloids in Garcinia cowa and Cryptolepis dubia, while the dichloromethane extract compound was discovered in Suregada multiflora, Capparis micracantha and Salacia chinensis. All samples extracted with 70% methanol did not contain any alkaloid compounds. Terpene was found in the hexane extracted compounds. Conclusions: These findings suggested that Ochna integerrima (Lour.) Merr. is a potent source of medicinal phytochemical compounds that could lead to its use as medicinal products.
Keywords: Flavonoids; Ochna integerrima (Lour.) Merr.; Phytochemical compounds; TLC